The first Irrigated Plantation of Rajasthan - Singh, Bharat (Indian Forester, 1963)
North-western Rajasthan is an arid waste covered with sand dunes and characterized by extremes of adverse climatic factors. The soils are sandy and water-table very deep. The area does not support any tree crop worth the name, but is being gradually transformed into prosperous colonies on account of the introduction of irrigation by Gang-Canal, Bhakra Canals and the Rajasthan Canal system. In order to meet the demand of forest produce for the new colonies and to achieve the target of forest area as enunciated in the National Forest Policy, irrigated forest plantations were started in 1958. Irrigation was available only for four months, from July to October. Shisham (Dalbergia sissoo) has done well and the success achieved in adequately irrigated patches, is encouraging. The article describes the salient features, technique and various problems of the first irrigated plantation, analyses the causes of failures and suggests remedial measures